Working Principle and Advantages of The Fsm-230 Solar Panel With Tempered Glass And Anodized Aluminum Frame - Karimov Abdusamat Ismonovich; Ismanov Mukhammadziyo Abdusamat ugli (Emerging Frontiers Library for The American Journal of Engineering and Technology, 2025)
This article describes the main design features, technical characteristics and scope of application of the FSM-230 polycrystalline solar photovoltaic module (230 W). The module consists of an anodized aluminum frame and tempered glass, and has high mechanical strength. Silicon photocells are protected from external environmental influences and mechanical damage due to the fact that they are placed between protective layers based on lamination technology. The FSM-230 module is used in autonomous and backup power supply systems, and together with a charge regulator, battery and inverter, it forms an independent power supply complex. The voltage at the open contacts of the module is 36.6 V, the operating current is 7.8 A, the short-circuit current is 8.42 A, and the efficiency is 16–18%. A plastic waterproof contact box (IP65) and bypass diodes ensure reliable operation of the module. The manufacturer guarantees a 25-year service life of the module and long-term maintenance of power at 80–90%.